A ready-mixed full-solid-waste high-performance pervious concrete and a preparation method thereof
Patent Information
- Application Number
- CN202410799652.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-20
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-06-20
AI Technical Summary
为提高全固废透水混凝土的强度,主要有以下两种方法:(1)提高激发剂的碱度,但这会导致地聚合物初凝时间变短,甚至导致闪凝;(2)将再生骨料放入高浓度碱液浸泡,对再生骨料表面的微观裂缝和孔洞修复,提高再生骨料的力学性能,但这会导致整个反应体系的碱度提高,不利于实现全固废透水混凝土的预拌
[0030]有益效果:本发明和现有技术相比,具有如下显著性特点:
Smart Images

Figure CN118754710B_ABST
Abstract
Description
Technical Field
[0001] This invention pertains to concrete and its manufacturing methods, specifically to a premixed high-performance permeable concrete made entirely from solid waste and its preparation method. Background Technology
[0002] Traditional silicate cement manufacturing emits significant amounts of greenhouse gases, resulting in a severe imbalance between solid waste generation and utilization. This necessitates utilizing solid waste in concrete production to promote green and sustainable development. Ready-mixed concrete allows for thorough mixing and uniform dispersion during transportation, reducing air content, shrinkage, and cracking, ensuring consistent and uniform concrete quality, improving project quality, and minimizing waste and pollution generated during on-site construction. Therefore, ready-mixed, all-solid-waste high-performance permeable concrete better meets the needs of construction waste management.
[0003] Recycled aggregate permeable concrete is typically an eco-friendly concrete material made by mixing, molding, and hardening cementitious materials, single-graded recycled aggregates, admixtures, and additives. The overall mechanical properties (compressive strength, flexural strength, etc.) of recycled aggregate permeable concrete are mainly determined by the bonding ability of the cementitious materials between aggregates within the geopolymer system and the mechanical properties of the cementitious materials themselves. This is the formation mechanism of the mechanical properties of recycled aggregate permeable concrete. However, given the relatively weak mechanical properties of recycled aggregates and the porous structure of permeable concrete, its strength is relatively low while maintaining permeability, especially its flexural strength. Furthermore, the rapid setting characteristic of geopolymer systems makes it difficult to implement pre-mixing technology to adapt to industrial development. These are the material challenges of recycled aggregate permeable concrete.
[0004] Chinese patent application number 202111244876.7 discloses a high-strength permeable geopolymer concrete made entirely from solid waste and its preparation method. This method improves the compressive strength and permeability of the permeable concrete by introducing geopolymer cementitious materials to bind recycled coarse aggregates and combining them with a rosin resin-based foaming agent to increase the porosity of the geopolymer concrete. However, this method does not solve the problem of low flexural strength in permeable concrete. Furthermore, due to the short initial setting time and poor initial fluidity of the geopolymer, it is difficult to achieve pre-mixing functionality. In addition, this patent uses recycled aggregates from recycled construction waste materials but does not utilize recycled powder.
[0005] Chinese patent application number 202210797434.3 discloses a high-strength premixed permeable concrete and its preparation method. The cementitious material in this patent is cement, and the aggregate is basalt. A premixing agent is used to increase the flow rate, initial setting time, and water retention capacity of the concrete, thereby improving the compressive strength of the permeable concrete and achieving the premixing function. However, the method in this patent cannot achieve the premixing of all-solid-waste permeable concrete.
[0006] Chinese patent application number 202211023696.0 discloses a permeable concrete containing porous hybrid fiber-modified recycled aggregate and its preparation method. By self-producing a porous carbon fiber and adding it to the recycled aggregate, the resulting concrete exhibits high strength and high toughness, achieving the reuse of the recycled aggregate. However, this method requires electrospinning, high-temperature carbonization, and ultrasonic treatment, and the incorporation of porous carbon fiber reduces the permeability coefficient of the permeable concrete, and pre-mixing is not possible.
[0007] Chinese patent application number 202210307967.9 discloses a method for preparing high-strength concrete using construction waste. The method involves soaking recycled aggregate in a solution made of silica fume, fly ash, slag, naphthalene-based water-reducing agent, and water. Sodium hydroxide is used to activate the silica fume, fly ash, and slag, and carbon dioxide is then introduced to repair surface defects in the recycled aggregate. However, this method involves continuous high-temperature treatment of the recycled aggregate, which can easily lead to micro-cracks or breakage due to thermal expansion and contraction. It also causes the loss of crystalline water and attached moisture from the aggregate, reducing its adhesion. Furthermore, the concrete prepared by this method still uses cement, natural coarse aggregate, and other components, and cannot achieve pre-mixing functionality.
[0008] Chinese patent application number 202310062465.9 discloses a premixed permeable concrete material made from recycled aggregate and its preparation process. In this method, cement is used as the cementitious material. To improve the strength of the permeable concrete, the recycled aggregate needs to be soaked in a high-concentration alkaline solution beforehand, increasing the alkalinity of the entire reaction system. To achieve the premixing function, the dosage of the retarding component needs to be increased, limiting the strength growth of the premixed permeable concrete. The premixed permeable concrete prepared by this method still has a strength grade lower than C25 after 28 days of curing, and this method cannot achieve the premixing of permeable concrete made entirely from solid waste.
[0009] In summary, permeable concrete made entirely from solid waste basically activates the silicon and aluminum in the solid waste through a high-alkalinity activator, forming a geopolymer cementitious material. This geopolymer cementitious material coats the recycled aggregate, and after the cementitious material hardens, the permeable concrete develops strength. The mechanical properties of permeable concrete are jointly determined by the mechanical properties of the aggregate and the cementitious material coating it. To improve the strength of permeable concrete made entirely from solid waste, there are two main methods: (1) increasing the alkalinity of the activator, but this will shorten the initial setting time of the geopolymer, or even cause flash setting; (2) soaking the recycled aggregate in a high-concentration alkaline solution to repair the micro-cracks and pores on the surface of the recycled aggregate, thereby improving the mechanical properties of the recycled aggregate, but this will increase the alkalinity of the entire reaction system, which is not conducive to the pre-mixing of permeable concrete made entirely from solid waste. Therefore, from the perspective of existing technology, the high strength and pre-mixing function of permeable concrete made entirely from solid waste are contradictory. Achieving high strength and pre-mixing of all-solid-waste permeable concrete is a technical challenge that must be overcome in the construction of zero-waste cities and sponge cities. It is necessary to develop a new technology to prepare high-strength pre-mixed all-solid-waste high-performance permeable concrete materials, which is of great significance and value to promoting the construction of zero-waste cities, sponge cities and the rapid development of the permeable concrete industry. Summary of the Invention
[0010] Purpose of the invention: In order to overcome the shortcomings of the existing technology, the purpose of this invention is to provide a premixed high-performance permeable concrete with good toughness, good permeability and high compressive strength. Another purpose of this invention is to provide a method for preparing premixed high-performance permeable concrete with a short curing cycle and simple operation.
[0011] Technical solution: The present invention provides a premixed high-performance permeable concrete made from all solid waste, comprising the following components by weight: 55-65 parts recycled aggregate, 25-45 parts cementitious material, 0.475-4.75 parts alkylbenzene sulfonate foaming agent, 0.6-2 parts potassium methylsilicate, 0.95-2.85 parts nano-alumina, 0.5-2 parts PE fiber, 0.2-0.7 parts lime, 28-38.5 parts sodium silicate aqueous solution, 2-5 parts glycerol carbonate, and 1-3 parts premixing agent;
[0012] The premixed agent comprises the following substances by mass percentage: 10–22 wt% polycarboxylate superplasticizer, 15–20 wt% fly ash, 0.7–1.5 wt% diethyldiallyl ammonium chloride, 1–2.1 wt% triethanolamine, and the balance being water.
[0013] Furthermore, the particle size of the recycled aggregate is 5–25 mm.
[0014] Furthermore, the cementitious material is recycled micro powder with an apparent density of 2300 kg / m³. 3 ~2700kg / m 3 Specific surface area is 300m²2 / kg~700m 2 / kg, water requirement ratio is 100%, activity index is 60% to 70%.
[0015] Furthermore, the amount of alkylbenzene sulfonate type foaming agent added is 0.5 to 5 wt% of the total mass of recycled aggregate and cementitious materials.
[0016] Furthermore, the amount of nano-alumina added is 1 to 3 wt% of the total mass of recycled aggregate and cementitious materials.
[0017] Furthermore, the nano-alumina has a Mohs hardness of 8–10 and a microhardness of 18–20 GPa. Preferably, the nano-alumina has a Mohs hardness of 9.5.
[0018] Furthermore, the diameter of the PE fibers is 5–10 mm, and the volumetric content is 0.5–1.5 g / cm³. 3 Preferably, the diameter of the PE fiber is 6 mm.
[0019] Furthermore, the total mass ratio of recycled aggregate and cementitious material to the sodium silicate aqueous solution is 1 kg: 300-500 mL.
[0020] The preparation method of the above-mentioned premixed all-solid-waste high-performance permeable concrete includes the following steps:
[0021] (1) After mixing the cementitious material, PE fiber, and lime at low speed, add the recycled aggregate, mix at low speed until uniform, add the alkylbenzene sulfonate foaming agent, glyceryl carbonate, potassium methyl silicate, and nano alumina, and mix quickly to obtain a solid mixture.
[0022] (2) Add sodium silicate aqueous solution to the solid mixture obtained in step (1), stir, add premixing agent and continue stirring to obtain all solid waste geopolymer concrete slurry;
[0023] (3) Transfer the all-solid waste geopolymer concrete slurry obtained in step (2) into the mold for curing, demold, and obtain pre-mixed all-solid waste high-performance permeable concrete.
[0024] Furthermore, in step (1), the speed of low-speed stirring is 350-500 r / min, and the speed of high-speed stirring is 800-1000 r / min.
[0025] Furthermore, in step (3), the curing time is 24 hours at room temperature. Since the early strength of the geopolymer is high, 28 days of curing is not required.
[0026] Technical principle:
[0027] 1. To achieve the high fluidity, retarded setting, and water retention properties of permeable concrete made from solid waste, potassium methylsilicate can react with the surface of recycled powder to form an adsorption layer, altering the surface charge properties and reducing the adsorption of water by recycled aggregates and powders, thus achieving a water-reducing effect. Simultaneously, the silanol groups in potassium methylsilicate dehydrate and crosslink with the silanol groups on the surface of aggregates and recycled powders, forming a hydrophobic layer that hinders water evaporation and improves the fluidity and water retention capacity of the permeable concrete. Polycarboxylate superplasticizers possess superdispersibility of dispersed particles and high stability in the dispersion system, effectively improving slurry fluidity. Glyceryl carbonate esters hydrate to glycerol in an alkaline environment composed of lime and other components. Simultaneously, the alcohol functional groups in the hydrolysis product of diethyldiallyl ammonium chloride, allyl alcohol, can form hydrogen bonds with water. Together with polycarboxylate superplasticizers, they reduce the surface tension of water, exhibiting excellent slump retention and viscosity reduction capabilities. When sodium silicate aqueous solution is added, it reacts with glycerol, allyl alcohol and other organic compounds in the slurry to form organosilicon compounds. These compounds then form a silicon oxide film on the surface of the geopolymer particles, reducing the reaction rate of alkali-activated slag materials, slowing down the reaction process of the geopolymer slurry, prolonging the setting time and improving fluidity.
[0028] 2. To improve the mechanical properties of permeable concrete made entirely from solid waste, glycerol carbonate, under the action of potassium methylsilicate, can penetrate into the tiny gaps in the recycled aggregate and hydrolyze to release carbonate ions in an alkaline environment. The carbonate ions can react with cementitious materials and alkaline components such as lime to form carbonate products, which repair the micro-cracks on the surface of the recycled aggregate. In addition, potassium methylsilicate also reacts with free calcium ions on the aggregate surface to generate calcium silicate. The calcium silicate reacts with carbonate ions to generate calcium carbonate, which further repairs the surface defects of the recycled aggregate, increases the apparent density of the recycled aggregate, and improves its mechanical properties.
[0029] 3. To improve the permeability of all-solid-waste permeable concrete, geopolymer cementitious material, as an inorganic cementitious material, has good bonding performance with recycled aggregate. When combined with alkylbenzene sulfonate foaming agent, it forms a continuous porous structure in the concrete body, which can improve the porosity of the material while ensuring the strength of the concrete, thereby improving the permeability of the concrete.
[0030] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0031] 1. The resulting premixed high-performance permeable concrete made from solid waste has good compressive strength and flexural strength, good toughness, and its permeability, compressive strength and flexural strength are all higher than those of ordinary permeable concrete. It is beneficial to reduce solid waste emissions and can be widely used in road paving and other fields.
[0032] 2. It can improve the construction efficiency and quality of permeable concrete preparation, while ensuring the stability and reliability of permeability and mechanical properties;
[0033] 3. The preparation process does not involve heating or other steps, and the curing cycle is short, making it suitable for large-scale production. Attached Figure Description
[0034] Figure 1 This is a flowchart of the preparation process of the present invention. Detailed Implementation
[0035] The raw materials used in the following embodiments are:
[0036] Cementitious material: Recycled micro powder, derived from demolished building materials, preferably those with high CaO and SiO2 content, crushed to a particle size of less than 0.16 mm, with an apparent density of 2300 kg / m³. 3 ~2700kg / m 3 Specific surface area is 300m² 2 / kg~700m 2 / kg, water requirement ratio is about 100%, and activity index is 60% to 70%.
[0037] Recycled coarse aggregate: Recycled manufactured sand, derived from demolished building materials, crushed to a particle size between 5 and 25 mm.
[0038] Potassium methylsilicate solution: purchased from the market, with a mass concentration of 3-13%.
[0039] Alkylbenzene sulfonate foaming agent, lime, and glyceryl carbonate: sourced from the market.
[0040] PE fiber: purchased from the market, 6mm specification.
[0041] Nano-alumina: sourced from the market, with a Mohs hardness of 9.5 and a microhardness of 18–20 GPa.
[0042] Sodium silicate aqueous solution: purchased from the market, composition is Na2O·nSiO2, n is selected from 1.0 to 3.5.
[0043] The premixed agent includes: 18 wt% polycarboxylate superplasticizer, 18 wt% fly ash, 1.0 wt% diethyldiallyl ammonium chloride, 1.5 wt% triethanolamine, and the balance is water.
[0044] Example 1
[0045] Weigh the raw materials according to the following proportions by weight: 65 parts recycled aggregate, 30 parts cementitious material, 1.9 parts alkylbenzene sulfonate foaming agent (2% of the total mass of cementitious material and recycled aggregate), 1.3 parts potassium methylsilicate, 1.9 parts nano alumina (2% of the total mass of cementitious material and recycled aggregate), 1 part PE fiber, 0.2 parts lime, 33.25 parts / 47.5 mL sodium silicate aqueous solution (the ratio of total mass of recycled aggregate, cementitious material and sodium silicate aqueous solution is 1 kg: 500 mL), 3 parts glyceryl carbonate, and 2 parts premixing agent.
[0046] like Figure 1 A method for preparing premixed high-performance permeable concrete made from all solid waste includes the following steps:
[0047] (1) Add cementitious materials, PE fibers and lime to a mixer and stir at 350 r / min for 4 min. After mixing, add recycled aggregate and stir at 400 r / min for 4 min until uniform. Then add alkylbenzene sulfonate foaming agent, glyceryl carbonate, potassium methyl silicate and nano alumina. Continue to stir at 900 r / min for 2 min to obtain a solid mixture.
[0048] (2) Slowly add sodium silicate aqueous solution to the solid mixture obtained in step (1), stir for 3 minutes, add premixed agent and continue stirring for 5 minutes to obtain all solid waste geopolymer concrete slurry.
[0049] (3) Transfer the solid waste geopolymer concrete slurry obtained in step (2) into a steel mold with specifications of 70.7×70.7×70.7mm, use a table vibrator to vibrate for 60 seconds to remove air bubbles, and smooth the surface with a trowel. After curing at room temperature for 24 hours, it can be demolded to obtain premixed solid waste high-performance permeable concrete.
[0050] Example 2
[0051] The preparation method of this embodiment is the same as that of Example 1, and the other components are the same as those of Example 1. The only difference is that: 55 parts of recycled aggregate, 25 parts of cementitious material, 0.475 parts of alkylbenzene sulfonate foaming agent, 0.6 parts of potassium methylsilicate, 0.95 parts of nano alumina, 0.5 parts of PE fiber, 0.2 parts of lime, 28 parts of sodium silicate aqueous solution, 2 parts of glycerol carbonate, and 1 part of premix.
[0052] Example 3
[0053] The preparation method of this embodiment is the same as that of Embodiment 1, and the other components are the same as those of Embodiment 1. The only difference is that: 65 parts of recycled aggregate, 45 parts of cementitious material, 4.75 parts of alkylbenzene sulfonate foaming agent, 2 parts of potassium methylsilicate, 2.85 parts of nano alumina, 2 parts of PE fiber, 0.7 parts of lime, 38.5 parts of sodium silicate aqueous solution, 5 parts of glycerol carbonate, and 3 parts of premix.
[0054] Example 4
[0055] Weigh the raw materials according to the following mass proportions: 60 parts recycled aggregate, 35 parts cementitious material, 1.9 parts alkylbenzene sulfonate foaming agent, 1 part potassium methylsilicate, 1.9 parts nano alumina, 1.5 parts PE fiber, 0.4 parts lime, 33.25 parts sodium silicate aqueous solution, 4 parts glycerol carbonate, and 2 parts premix.
[0056] A method for preparing premixed high-performance permeable concrete made entirely from solid waste includes the following steps:
[0057] (1) Add cementitious material, PE fiber and lime to a mixer and stir at 500 r / min for 4 min. After mixing, add recycled aggregate and stir at 400 r / min for 4 min until uniform. Then add alkylbenzene sulfonate foaming agent, glyceryl carbonate, potassium methyl silicate and nano alumina. Continue to stir at 800 r / min for 2 min to obtain a solid mixture.
[0058] (2) Slowly add sodium silicate aqueous solution to the solid mixture obtained in step (1), stir for 3 minutes, add premixed agent and continue stirring for 5 minutes to obtain all solid waste geopolymer concrete slurry.
[0059] (3) Transfer the solid waste geopolymer concrete slurry obtained in step (2) into a steel mold with specifications of 70.7×70.7×70.7mm, use a table vibrator to vibrate for 60 seconds to remove air bubbles, and smooth the surface with a trowel. After curing at room temperature for 24 hours, it can be demolded to obtain premixed solid waste high-performance permeable concrete.
[0060] Example 5
[0061] Weigh the raw materials according to the following mass proportions: 62 parts recycled aggregate, 40 parts cementitious material, 2.04 parts alkylbenzene sulfonate foaming agent, 1.5 parts potassium methylsilicate, 2.04 parts nano alumina, 1 part PE fiber, 0.5 parts lime, 35 parts sodium silicate aqueous solution, 3 parts glycerol carbonate, and 3 parts premix.
[0062] A method for preparing premixed high-performance permeable concrete made entirely from solid waste includes the following steps:
[0063] (1) Add cementitious material, PE fiber and lime to a mixer and stir at 500 r / min for 4 min. After mixing, add recycled aggregate and stir at 400 r / min for 4 min until uniform. Then add alkylbenzene sulfonate foaming agent, glyceryl carbonate, potassium methyl silicate and nano alumina. Continue to stir at 1000 r / min for 2 min to obtain a solid mixture.
[0064] (2) Slowly add sodium silicate aqueous solution to the solid mixture obtained in step (1), stir for 3 minutes, add premixed agent and continue stirring for 5 minutes to obtain all solid waste geopolymer concrete slurry.
[0065] (3) Transfer the solid waste geopolymer concrete slurry obtained in step (2) into a steel mold with specifications of 70.7×70.7×70.7mm, use a table vibrator to vibrate for 60 seconds to remove air bubbles, and smooth the surface with a trowel. After curing at room temperature for 24 hours, it can be demolded to obtain premixed solid waste high-performance permeable concrete.
[0066] Comparative Example 1
[0067] The preparation method of this comparative example is the same as that of Example 1, and the other components are the same as those of Example 1, except that the addition of nano-alumina is omitted.
[0068] Comparative Example 2
[0069] The preparation method of this comparative example is the same as that of Example 1, and the other components are the same as those of Example 1, except that the addition of potassium methylsilicate is omitted.
[0070] Comparative Example 3
[0071] The preparation method of this comparative example is the same as that of Example 1, and the other components are the same as those of Example 1, except that the addition of alkylbenzene sulfonate type foaming agent is omitted.
[0072] Comparative Example 4
[0073] The preparation method of this comparative example is the same as that of Example 1, and the other components are the same as those of Example 1, except that the addition of lime is omitted.
[0074] Comparative Example 5
[0075] The preparation method of this comparative example is the same as that of Example 1, and the other components are the same as those of Example 1, except that the addition of PE fiber is omitted.
[0076] Comparative Example 6
[0077] The preparation method of this comparative example is the same as that of Example 1, and the other components are the same as those of Example 1, except that the addition of glyceryl carbonate is omitted.
[0078] Comparative Example 7
[0079] The preparation method of this comparative example is the same as that of Example 1, and the other components are the same as those of Example 1. The only difference is that the addition of the premix is omitted.
[0080] Performance testing experiments: High-strength permeable concrete was prepared according to the methods in each embodiment and comparative example, and the following performance tests were conducted:
[0081] (1) The initial slump, 90-minute slump loss and initial setting time were tested in accordance with DB32 / T 4163~2021 "Technical Specification for Application of Premixed Permeable Cement Concrete".
[0082] (2) The permeability coefficient shall be tested in accordance with the test method specified in CJJ / T135-2009 "Technical Specification for Permeable Cement Concrete Pavement".
[0083] (3) Compressive strength and flexural strength were tested in accordance with GB / T500-81-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete".
[0084] (4) The porosity was tested in accordance with DB11 / T775~2010 Technical Specification for Permeable Concrete Pavement.
[0085] The test results are shown in Table 1 below.
[0086] Table 1 Test data for different types of concrete
[0087]
[0088] Through Examples 1, 2, and 3, it can be observed that as the mass fraction of coarse aggregate decreases, the concrete strength decreases slightly, but not significantly. The reduction in the volume fraction of coarse aggregate also leads to a decrease in permeability and porosity. Simultaneously, the addition of alkylbenzene sulfonate foaming agents and nano-alumina can significantly improve the porosity of concrete, while glycerol carbonate can improve the initial fluidity of concrete. Therefore, to obtain materials with high porosity and permeability, it is recommended to use coarse aggregate with a mass fraction of approximately 65%. Furthermore, omitting alkylbenzene sulfonate foaming agents will severely reduce the porosity of the material; omitting potassium methylsilicate, nano-alumina, lime, and glycerol carbonate will reduce the compressive strength of the material; omitting PE fibers will reduce the flexural strength of the material; and omitting premixed agents will cause a comprehensive decline in concrete quality. After 90 minutes, the concrete completely loses its slump, exhibiting obvious hardening and setting, rendering it unsuitable for premixing and unable to meet engineering requirements.
[0089] Of the above embodiments, Embodiment 1 is the best embodiment.
Claims
1. A pre-mixed, all-solid-waste high-performance permeable concrete, characterized in that, It is composed of the following substances in parts by weight: 55-65 parts recycled aggregate, 25-45 parts cementitious material, 0.475-4.75 parts alkylbenzene sulfonate foaming agent, 0.6-2 parts potassium methylsilicate, 0.95-2.85 parts nano alumina, 0.5-2 parts PE fiber, 0.2-0.7 parts lime, 28-38.5 parts sodium silicate aqueous solution, 2-5 parts glycerol carbonate, and 1-3 parts premix; The premixed agent is composed of the following substances in mass percentage: 10-22 wt% polycarboxylate superplasticizer, 15-20 wt% fly ash, 0.7-1.5 wt% diethyldiallyl ammonium chloride, 1-2.1 wt% triethanolamine, and the balance being water; The nano-alumina has a Mohs hardness of 8-10 and a microhardness of 18-20 GPa. The preparation method of the premixed all-solid-waste high-performance permeable concrete includes the following steps: (1) After mixing the cementitious material, PE fiber, and lime at low speed, add the recycled aggregate and mix at low speed until uniform. Then add the alkylbenzene sulfonate foaming agent, glyceryl carbonate, potassium methylsilicate, and nano alumina and mix quickly to obtain a solid mixture. The speed of low-speed mixing is 350~500 r / min, and the speed of fast mixing is 800~1000 r / min. (2) Add sodium silicate aqueous solution to the solid mixture obtained in step (1), stir, add premixing agent and continue stirring to obtain all-solid waste polymer concrete slurry; (3) Transfer the solid waste geopolymer concrete slurry obtained in step (2) into the mold for curing, demold, and obtain premixed solid waste high-performance permeable concrete.
2. The premixed high-performance permeable concrete made from all solid waste as described in claim 1, characterized in that: The particle size of the recycled aggregate is 5~25mm.
3. The premixed high-performance permeable concrete made from all solid waste as described in claim 1, characterized in that: The cementitious material is recycled micro powder with an apparent density of 2300 kg / m³. 3 ~2700kg / m 3 Specific surface area is 300m² 2 / kg~700m 2 / kg, water requirement ratio is 100%, activity index is 60%~70%.
4. The premixed high-performance permeable concrete made from all solid waste as described in claim 1, characterized in that: The amount of the alkylbenzene sulfonate foaming agent added is 0.5 to 5 wt% of the total mass of the recycled aggregate and cementitious materials.
5. The premixed high-performance permeable concrete made from all solid waste as described in claim 1, characterized in that: The amount of nano-alumina added is 1 to 3 wt% of the total mass of recycled aggregate and cementitious materials.
6. The premixed high-performance permeable concrete made from all solid waste as described in claim 1, characterized in that: The total mass ratio of the recycled aggregate and cementitious material to the sodium silicate aqueous solution is 1 kg: 300~500 mL.
7. A method for preparing premixed high-performance permeable concrete from all solid waste according to any one of claims 1 to 6, characterized in that, Includes the following steps: (1) After mixing the cementitious material, PE fiber, and lime at low speed, add the recycled aggregate and mix at low speed until uniform. Then add the alkylbenzene sulfonate foaming agent, glyceryl carbonate, potassium methylsilicate, and nano alumina and mix quickly to obtain a solid mixture. The speed of low-speed mixing is 350~500 r / min, and the speed of fast mixing is 800~1000 r / min. (2) Add sodium silicate aqueous solution to the solid mixture obtained in step (1), stir, add premixing agent and continue stirring to obtain all-solid waste polymer concrete slurry; (3) Transfer the solid waste geopolymer concrete slurry obtained in step (2) into the mold for curing, demold, and obtain premixed solid waste high-performance permeable concrete.
Citation Information
Patent Citations
A high-strength permeable polymer concrete made entirely from solid waste and its preparation method
CN113831152B
High-strength concrete prepared from construction waste and preparation method of high-strength concrete
CN114671649A
Pervious concrete containing porous hybrid fiber modified recycled aggregate and preparation method thereof
CN115448657A
All-solid-waste high-strength water-permeable geopolymer concrete and preparation method thereof
CN113831152A
Premixed pervious concrete with high strength and preparation method thereof
CN115028415A